PENGARUH PENGGUNAAN CLOUD COMPUTING (GOOGLE DRIVE) TERHADAP KINERJA TENAGA PENGAJAR DI SEKOLAH MTsS MON MALEM BLANG BINTANG - Dhiyaul Abrar; Mira Maisura; Bustami Yusuf (UIN Ar-Raniry, 2017)
The use of google drive as a storage area cloud-based is considered able to improve working performance. This technology was introduced in the school MTsS Mon Malem in Aceh Besar region, in order to see the effect of using cloud technology in the working performance of teachers. After conducting several tests, including pre-test and post-test, we analyzed the data using SPSS to obtain the value of R which represents the effect of the use of google drive to the performance of teachers. The result of this work show that by using google drive the performance of the teacher is increasing